(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
Dysmetabolic nephropathies (DN) contribute to the development of urolithiasis in children, the occurrence of urinary tract infection and the development of secondary pyelonephritis, tubulointerstitial changes in the kidneys.